Craniomaxillofacial surgery planning based on 3D models derived from Cone-Beam CT data. (10th May 2013) - Adolphs, Nicolai; Liu, Weichen; Keeve, Erwin; Hoffmeister, Bodo
Abstract: Introduction: Individual planning of complex maxillofacial corrections may require 3D models which can be manufactured based on DICOM datasets. The gold standard for image acquisition is still high-resolution multi-slice computed tomography (MSCT). However, appropriate datasets for model fabrication can be acquired by modern Cone-Beam CT (CBCT) devices that have been developed specifically for maxillofacial imaging. The clinical utility of individual models fabricated on the basis of CBCT datasets was assessed. Methods: In five patients affected by different deficiencies of the maxillofacial skeleton, preoperative imaging was performed with ILUMA CBCT. Segmentation of hard tissues was performed manually by thresholding. Corresponding STL datasets were created and exported to an industrial service provider (Alphaform, Munich, Germany) specializing in rapid prototyping, and 3D models were fabricated by the selective laser sintering (SLS) technique. For variance analysis, landmark measurements were performed on both virtual and 3D models. Subsequently, maxillofacial surgery was performed according to the model-based planning. Results: All CBCT-based DICOM datasets could be used for individual model fabrication. Detailed reproduction of individual anatomy was achieved and a topographic survey showed no relevant aberrance between the virtual and real models. The CBCT-based 3D models were therefore used for planning and transfer of different maxillofacial procedures. Conclusions: CBCT-based datasets can be used for the fabrication of surgical 3D models if the correct threshold is set. Preoperative workflow and patient comfort is improved in terms of the fast-track concept by using this "in-house" imaging technique.